Insect pollinators' diversity of rapeseed (Brassica campestris var. toria) in Chitwan, Nepal - Pudasaini, R.; Thapa, R. B.; Chaudhary, N. K.; Tiwari, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
The abundance and diversity of rapeseed insect flower visitors were assessed by using insect pan traps, sweep net and visual observations at different blooming stage of rapeseed at Jutpani VDC, Chitwan district, Nepal during 2012-013. The pollinator fauna of rapeseed included twenty one species from six different insect orders. Hymenopteran (77.95%) species were the most abundant insects visiting rapeseed followed by Diptera (12.23%) and Lepidoptera (3.49%). Honeybees were the dominant group of pollinators and among honeybees, Apis mellifera L. was the most dominant one (36.34%) followed by Apis florea F. (12.45%), Apis cerana F. (11.14%) and Apis dorsata F. (5.68%). The higher abundance and diversity of pollinators were observed at 12:00 to 1:00 pm and the diversity was related to the crop blooming stage. Therefore, pollinator's friendly cultivation practices should be followed for conservation and management of insect pollinators for higher production and productivity of rapeseed crop under Chitwan condition. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, 73-78